7 9 4 + 7 9 2 + 1 7 9 2 + 79 + 1 = 8 0 2 A \frac{79 ^4+79 ^2+1}{79 ^2+79+1}=80 ^2-A

Algebra Level 2

233 233 237 237 235 235 231 231

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Saurabh Mallik
May 12, 2014

Let's assume: x = 79 x=79

Then, taking LHS we get:

7 9 4 + 7 9 2 + 1 7 9 2 + 79 + 1 = x 4 + x 2 + 1 x 2 + x + 1 \frac{79^{4}+79^{2}+1}{79^{2}+79+1} = \frac{x^{4}+x^{2}+1}{x^{2}+x+1}

So, factorizing the numerator we get:

x 4 + x 2 + 1 = ( x 4 + 2 x 2 + 1 ) x 2 x^{4}+x^{2}+1=(x^{4}+2x^{2}+1)-x^{2}

= ( x 2 + 1 ) 2 ( x ) 2 = ( x 2 + x + 1 ) ( x 2 x + 1 ) =(x^{2}+1)^{2}-(x)^{2}=(x^{2}+x+1)(x^{2}-x+1)

So, x 4 + x 2 + 1 = ( x 2 + x + 1 ) ( x 2 x + 1 ) x^{4}+x^{2}+1=(x^{2}+x+1)(x^{2}-x+1)

So, x 4 + x 2 + 1 x 2 + x + 1 = ( x 2 + x + 1 ) ( x 2 x + 1 ) x 2 + x + 1 \frac{x^{4}+x^{2}+1}{x^{2}+x+1}=\frac{(x^{2}+x+1)(x^{2}-x+1)}{x^{2}+x+1}

Canceling ( x 2 + x + 1 ) (x^{2}+x+1) , we get:

( x 2 + x + 1 ) ( x 2 x + 1 ) x 2 + x + 1 = x 2 x + 1 \frac{(x^{2}+x+1)(x^{2}-x+1)}{x^{2}+x+1}=x^{2}-x+1

x 2 x + 1 = 7 9 2 79 + 1 = 7 9 2 78 x^{2}-x+1=79^{2}-79+1=79^{2}-78

Now, the equation is: 7 9 2 78 = 8 0 2 A 79^{2}-78=80^{2}-A

A 78 = 8 0 2 7 9 2 A-78=80^{2}-79^{2}

A 78 = ( 80 + 79 ) ( 80 79 ) A-78=(80+79)(80-79)

A 78 = 159 × 1 A-78=159\times1

A = 159 + 78 A=159+78

A = 237 A=237

So, the answer is: A = 237 A=\boxed{237}

i did that way too. ^_^

세준 권 - 6 years, 10 months ago
Blesson Roy
Mar 31, 2014

Considering only the LHS and taking units digit only we get [(1+1+1)/(1+9+1)] = 3/1 = 3. Hence the LHS is 3. RHS must be equal to LHS. Comsidering RHS gives us units digit of 80^2 = 0. Hence to get RHS = 3; The only number possible is one having units digit 7. (Since 80^2 - 7 = Units digit 3) Hence the answer is 237.

Madhuri Dholakiya
Mar 19, 2014

formula is (x^4+X^2+1)=(x^2+x+1)(x^2-x+1) where x=79 put on formula get (79^2-79+1)=80^2-A after simplification can get a=237

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...